Analyzing Driver's Facial Muscle Movements on a Highway. (September 2022) - Mostowfi, Sara; Kim, Jung Hyup
Driving could be affected by various external variables such as traffic congestion, roadside infrastructure, and in-cabin situations. Although those factors might influence a driver's cognitive behavior, not many studies have been done to understand drivers' emotional changes corresponding to the external driving factors. To address this research gap, the current study aimed to analyze and compare what facial expressions drivers made when they drove straight, exited/entered or near the shoulder of a highway. The human-inthe-loop (HTIL) simulation experiment was conducted, and drivers' facial muscle movements were recorded while they drove straight, exited/entered, and near the shoulders of a highway. According to the results, we found that drivers opened their mouths wider while exiting and entering the highway. Also, the movements of three facial muscles were more evident when they entered or exited the highway and driving near the shoulder. The outcome of this study might provide knowledge to human-computer-interaction practitioners and engineers on designing advanced driving assistance systems.